PENGALOKASIAN ANGGARAN DANA DESA DAN PEMBERDAYAAN MASYARAKAT NAGARI KOTO ANAU TAPAN - Mua'rif, Zul Ihsan; Nurdin, Zulkifli; Syarif, Dafiar; Bustami, Alek Wissalam; Azhar, Azhar (Institut Agama Islam Negeri Kerinci, 2023)
This research aims to determine the use of village budget funds for community empowerment. Various problems are being faced, such as welfare, public services, and fund management. The research was conducted using interviews and direct observation. The results show that fund management is carried out through deliberation in accordance with nagari customs. Most of the village funds are used for village operational costs which should be allocated to other activities. Aspirations as a form of deliberation also take the form of physical development because the level of education is still relatively low. So the expected solution includes providing education for the community so that they can get ideas that can advance their region. This is an important note for the nagari to prioritize education by creating several education-oriented programs so that it is hoped that the village funds distributed can answer every community need.